WANITA DAN DUNIA HIBURAN (Studi Kasus Wanita Bekerja di Billiard Kota Pekanbaru) - Muliani, Indri; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted because of the development of the world of night entertainment in Pekanbaru and more female workers who work in one of the world night entertainment such as billiard. The purpose of this research is to analyzes about women’s life who working as a score girl in billiard. The writer using qualitative methods with the purposive sampling technique to set the informant, the author sets 5 women's score girl to become an informant in order to give an explanation about life of the score girl using habitus theory. The results of this study found that living a life by working as a score girl is not easy to be lived by the five informant researchers. The consequences that must be accepted because they choose a different work of work that is commonly done by other women is like the bad views of the community they have been familiar with and they continue to live daily activities Like a young woman in general. The attention of a family that is also not too intense makes them can still be free to undergo daily life in Pekanbaru. Basic life of women who work as a score girl there are several aspects, namely social such as the relationship between the score girl with the surrounding environment, the economy is income and about the financial score girl, the culture is the provision or teaching that Can score girl from her parents and family, as well as symbolic of appearances that must be noticed and in the watchful by the score girl to keep it look beautiful and interesting. Keywords: Score Girl, Billiard, Habitus